Inflammatory linear verrucous epidermal nevus treated successfully with crisaborole ointment in a 5‐year‐old boy. Issue 3 (5th March 2019) - Barney, Emily; Prose, Neil S.; Ramirez, Mary
Abstract: Inflammatory linear verrucous epidermal nevus (ILVEN) is a chronic, a linear, or whorled array of inflammatory, following the lines of Blaschko. Treatment of ILVEN is challenging with numerous therapies of varying degrees of success reported. We present a case of ILVEN in a 5‐year‐old‐boy, treated successfully with crisaborole 2% ointment. This brief report suggests that there may be additional cellular immunologic pathways responsible for the presentation of ILVEN that may be explained by management with crisaborole use.